Penanggulangan depresi anak pascaerupsi Gunung Merapi melalui pelatihan permainan berbasis kearifan budaya lokal pada guru dan orang tua murid taman kanak-kanak - Sumarni Sumarni; Cecep Sugeng Kristanto; Andrian Fajar Kusumadewi; Santi Yuliani; Nanda Kusumaningrum (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2019)
Child mental health is a top priority for the 2015 Indonesian National Child Program with the vision of enabling Indonesian children to grow and develop in good health, to be protected and to actively participate. The Mount Merapi eruption had a major impact on the lives of the people living nearby. Many livelihoods came to a halt, forcing some people to work as sand miners until late at night. As a result, children receive less time and attention from their mothers. The combination of traumatic events and unsuitable parenting increase the tendency for depression, a grave health problem in children. Lack of awareness among parents and teachers can cause a delay in the detection and treatment of depression in children, which will negatively affect the children’s school performance and future. This community service and research project held a training on childhood depression. Twelve teachers, 55 parents, and 55 students from Kuncup Mekar Kindergarten and Aisyiyah Bustanul Athfal (ABA) Kindergarten, Cangkringan, Sleman participated in the training. The training included early detection of childhood depression, game modules based on traditional games, game equipment, and the Child Depression Inventory (CDI). The output of the training was evaluated by comparing pre-test and post-test results, as well as interviews. The tendency of depression in the participating children before and after training was assessed using CDI. After the training, the average level of knowledge on early detection and prevention of depression in children increased from 33.7 to 68.0, while the average skill level in playing traditional games increased from 43.9 to 85.2. The number of students with depression tendencies declined from 37 children (67%) to 16 (39%). Traditional game training can increase the knowledge and skills of teachers and parents of kindergarten students in tackling depression in children after the eruption of Mount Merapi.